Ruptured ectopic pregnancy presenting as an irreducible inguinal hernia - Prasannan, Subhita; Jabar, Mohd Faisal; Alif Gul, Yunus Gul (ARSMB-KVBMG, 2004)
An inguinal hernia that suddenly becomes irreducible may be secondary to a variety of other underlying conditions which can occasionally mislead the attending surgeon. Benign, inflammatory or neoplastic processes, as well as surgical emergencies such as intraperitoneal or retroperitoneal haemorrhage, have all been previously reported to mimic an inguinal hernia that suddenly becomes irreducible with or without clinical features of strangulation. We add an additional interesting presentation to this list in the form of a ruptured ectopic pregnancy, which is the first such case reported in the literature. A swelling in the groin may be much more complicated than it seems on superficial consideration and good clinical acumen is constantly required in managing such cases if a satisfactory outcome without any morbidity is to be expected.